Bioetanolproduktion - Ur ett hållbart och tekniskt perspektiv - Dyvermark, Arvid; Andersson, Johan (My University, 2017)
Fossil fuels have, since several centuries ago, been mankind’s primary energy resource, but the use of fossil fuels also has contributed to large-scale damage to the environment. To reduce mankind’s negative impact on the environment, research into sustainable fuels have been done to find a fuel that is able to provide both to the current energy consumption from fossil fuels as well as reduce greenhouse gas emissions. Bioethanol is a renewable fuel which can be produced by biologically degradable raw materials and then be used as fuel. It is an advanced process to produce bioethanol and earlier research has resulted in several different production methods. The problem with bioethanol production is how energy efficient and environmentally friendly the different production methods are to maintain a profitable application. The purpose of this study is to investigate bioethanol production from waste originating from the food industry in the form of cereal based raw materials, regarding energy balance, environmental friendliness and technical design to maintain an efficient production. The result in this study is based on earlier research on the subject as well as a case study on a full-scale bioethanol production facility at Företag AB. By gathering information from earlier research and comparing theoretical data with real data, a reliable comparison is given to answer the studies research questions. The result indicated that bioethanol production from cereal based raw materials, more specifically discarded bakery products, is not sustainable with regard to energy consumption and greenhouse gas emissions both before and after production.
Keywords: Energi; Transport; Hållbar utveckling; Farkostteknik; Energy; Transport; Sustainable Development; Vehicle Engineering